In vitro and in vivo fitness costs associated with Mycobacterium tuberculosis RpoB mutation H526D. (July 2017) - Rifat, Dalin; Campodónico, Victoria L; Tao, Jing; Miller, James A; Alp, Alpaslan; Yao, Yufeng; Karakousis, Petros C
Aim: There is controversy regarding the potential fitness costs of rifampicin (RIF) resistance-conferring mutations in the Mycobacterium tuberculosis (Mtb) rpoB gene. We characterized the pathogenicity of an Mtb RpoB H526D mutant.Materials & methods: A mutant containing the RpoB H526D mutation was isolated from wild-type Mtb grown on RIF-containing plates and complemented for determination of in vitro and in vivo fitness costs.Results: The RpoB H526D mutant showed reduced survival relative to control strains during progressive hypoxia and delayed growth following resuscitation from nutrient starvation (p < 0.05), which was associated with reduced expression of the resuscitation-promoting factor genes rpfB, rpfC and rpfE . Relative to the isogenic wild-type strain, the mutant showed significantly attenuated growth and long-term survival as well as reduced inflammation in mouse lungs.Conclusion & future perspective: Our data suggest that RpoB H526D mutation confers a fitness cost during growth-limiting conditions in vitro and in mouse lungs.